Internal hernia to the retrosternal space is a rare complication after minimally invasive esophagectomy: three case reports - Takuji Sato; Takeo Fujita; Hisashi Fujiwara; Hiroyuki Daiko (Surgical Case Reports)
Abstract Background Minimally invasive esophagectomy is considered a beneficial approach to esophageal cancer, although a hiatal hernia occurs more frequently in this approach than in open esophagectomy with reconstruction via the mediastinal route. Development of an internal hernia to the retrosternal space is not a recognized complication of reconstruction via the retrosternal route after esophagectomy. We herein report three cases of the development of an internal hernia to the retrosternal space after minimally invasive esophagectomy. Case presentation Thoracolaparoscopic esophagectomy with cervical anastomosis by retrosternal route reconstruction was performed in all three cases. All patients were men ranging in age from 60 to 80 years. Two patients had abdominal pain, and one had experienced syncope. All patients were diagnosed by computed tomography with an internal hernia to the retrosternal space and thoracic cavity (retrosternal hernia) without ischemic change to the incarcerated intestine. Two patients received medical therapy to relieve their intra-abdominal pressure, which allowed for a successful reduction of the intestine into the abdomen. Open laparotomy was performed to repair the hernia in the third patient. After reducing the intestine into the abdomen, reefing of the retrosternal orifice was performed, and the gastric conduit was anchored to the abdominal wall. No relapse occurred in three cases throughout follow-up. Conclusion Hiatal hernia is a well-recognized complication after minimally invasive esophagectomy; however, retrosternal hernia is a rare complication following this procedure. Based on the present report, if no ischemic change is present in the herniated intestine, two types of potentially curative treatments are available: medical or surgical. As minimally invasive esophagectomy is performed more frequently, retrosternal hernia may become an increasingly more common complication in the near future.